A methodology for solid modelling in a virtual reality environment - Zhong, Yongmin; Ma, W.; Shirinzadeh, B. (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
This paper presents a methodology for solid modelling in a virtual reality (VR) environment. Solid modelling in the VR environment is precisely performed in an intuitive manner through constraint-based manipulations. A hierarchically structured and constraint-based data model is developed to support solid modelling in the VR environment. Constraint-based manipulations are realized by allowable motions for precise 3D interactions in the VR environment. A mathematical matrix is presented for representing allowable motions. A procedure-based degree-of-freedom combination method for 3D constraint solving is presented for deriving the allowable motions from constraints. A rule-based constraint recognition engine is developed for both constraint based manipulations and implicitly incorporating constraints into the VR environment. A prototype system has been implemented to testify the feasibility of the presented methodology.